Non‐intrusive real‐time monitoring of PV generation at inverters using Internet of photovoltaics. Issue 16 (1st August 2017) - Pulipaka, S.; Ramesh, A.; Kumar, R.; Bora, B.; Kumar, S.; Singh, S.K.
Abstract : A non‐intrusive mechanism of gathering real‐time performance of inverter data is explained. Network architecture was designed to get this data from various inverters in an area of 200 acres with synchronised time interval for comparing the performance of inverters of different topology and solar panel technologies at same climatological conditions. Ecosystem of things as termed it the Internet of photovoltaics was created at the National Institute of Solar Energy in India, where all the inverter nodes were in the same network, communicating with a centralised server for receiving commands and sending required information.